A Collagen Membrane Pretreated with Citrate Promotes Collagen Mineralization and Bone Regeneration - Qi Zhang; Yewen Zhong; Xinlin He; Sui Mai (Journal of Functional Biomaterials, 2025)
Purpose: Collagen membranes with biomimetic mineralization are emerging as promising materials for bone regeneration, owing to their high biocompatibility. In this study, we developed a biogenic collagen membrane by combining citrate (C) pretreatment and carboxymethyl chitosan (CMC)-mediated mineralization and further evaluated its bone healing potential. Methods: C-CMC collagen membranes were prepared by lyophilization. The mineral composition and content were tested through X-ray diffraction (XRD), Fourier transform infrared (FTIR), and thermogravimetric analysis (TGA). The micromorphology was observed using transmission electron microscopy (TEM), scanning electron microscopy (SEM), and scanning probe microscopy (SPM). Physical and mechanical properties, including the swelling rate, porosity, hydrophilicity, tensile strength, Young’s modulus, degradation, and barrier function, were also evaluated. Bone mesenchymal stem cells (BMSCs) were cultured in vitro to observe their behavior. An in vivo critical-size rat calvarial defect model was used to validate the effects of the membrane on bone regeneration. Results: The C-CMC collagen membrane was successfully synthesized as a collagen–hydroxyapatite complex with intrafibrillar mineralization, exhibiting improved mechanical properties and an optimal swelling rate, porosity, hydrophilicity, and degradation rate. Additionally, the C-CMC collagen membrane promoted BMSC proliferation, adhesion, and osteogenesis while preventing epithelial cell infiltration. In vivo experiments indicated that C-CMC collagen membranes significantly stimulated bone regeneration without causing systemic toxicity. Conclusions: Our findings suggest that the C-CMC collagen membrane possesses satisfactory physical and mechanical properties, along with good biocompatibility and efficacy in bone defect regeneration, making it a potential candidate for a bioactive guided bone regeneration membrane in clinical applications.